Editorial of Special Issue “Fibrodysplasia Ossificans Progressiva: Studies on Disease Mechanism towards Novel Therapeutic Approaches” - Roberto Ravazzolo (Biomedicines, 2022)
The Special Issue on “Fibrodysplasia Ossificans Progressiva: Studies on Disease Mechanism towards Novel Therapeutic Approaches” has published interesting and useful review articles and original experimental articles on fibrodysplasia ossificans progressiva (FOP), a very rare genetic disorder for which much effort is being devoted to search for a cure. In this editorial, I briefly cite the essential content of all the published articles.